Efficient Large-Scale Removal of Poly(methyl methacrylate) Layers by Using a Methyl Isobutyl Ketone Solution - Son, B. H.; Ahn, Y. H. (Journal of the Korean Physical Society, 2019)
In this study, we proposed a fast and effective technique to remove residual poly(methyl methacrylate) (PMMA) after its use as a supporting layer for transferring graphene films on a large scale with high productivity. We utilized a methyl isobutyl ketone (MIBK) solution, which is commonly used to develop PMMA layers, for an e-beam lithography process. This was done because MIBK molecules tend to inflate the PMMA layer, weakening the link between PMMA and the graphene surface. Field-effect transistors were fabricated on the transferred graphene, with which we addressed the Dirac points and their carrier motilities. We observed that due to the reduced p-doping effects, the Dirac points were located closer to the zero-gate bias compared to those obtained using the acetone treatment. Finally, the average device mobility reached 5400 and 3900 cm2/Vs for holes and electrons, respectively. These values are more than five times the values obtained using the conventional acetone treatment.
Keywords: Field-effect transistor; Graphene; MIBK; PMMA